Syncope as Initial Presentation of Kommerell Diverticulum - Cohen, Ronny; Loarte, Pablo; Garcia, Christine; Diaz, Lizmer; Mirrer, Brooks (International Journal of Angiology, 2012)
Kommerell diverticulum (KD) is an aortic arch diverticulum at the origin of an aberrant subclavian artery. It is a rare anatomical anomaly that can be associated with a double aortic arc, a left aortic arch, and anomalous origin of the right subclavian artery or a right aortic arch with anomalous left subclavian artery. We present a case of KD presenting initially as syncope, as well as a review of the literature of this rare syndrome, including diagnosis, imaging techniques, and current surgical treatments.
Keywords: diverticulum; Kommerell; left subclavian artery; syncope